Penyuluhan Protokol 3M Dalam Pencegahan COVID-19 Pada Penduduk Kelurahan Pluit, Kecamatan Penjaringan, Jakarta Utara - Juni Chudri; Fransisca Chondro; Astri Handayani (CV. Multi Kreasi Media, 2023)
COVID-19 is a disease caused by a variant of SARS-COV2 virus. The symptoms of this disease are fever, cough, malaise, myalgia, short of breath that can happened in 2 – 14 days after infection. The transmission of this disease happened when droplet of a patient is dispersed in the air and the inhaled by other people or by using object that has been contaminated by the COVID-19 patients. The first case of COVID-19 in Indonesia was reported on March 2nd, 2020 and soon after there’s an increase in morbidity and mortality rate regarding this disease. There are some ways that can be done to reduce the transmission of this disease such as wearing mask properly, handwashing, and physical distancing. Advice regarding the health protocol was not only issued by Ministry of Health of Indonesia, but also by World Health Organization. Another way to reduce the transmission of this disease is to isolate the patient and implement the physical distancing between the patient and caregiver.